Tanshinone IIA: New Perspective on the Anti-Tumor Mechanism of A Traditional Natural Medicine - Zhang, Wenfeng; Liu, Cun; Li, Jie; Lu, Yiping; Li, Huayao; Zhuang, Jing; Ren, Xin; Wang, Mengmeng; Sun, Changgang (The American journal of Chinese medicine (1979), 2022)
The search for natural and efficacious antineoplastic drugs, with minimal toxicity and side effects, is an important part of antitumor drug research and development. Tanshinone IIA is the most evaluated lipophilic active component of . Tanshinone IIA is a path-breaking traditional drug applied in cardiovascular treatment. It has also been found that tanshinone IIA plays an important role in the digestive, respiratory and circulatory systems, as well as in other tumor diseases. Tanshinone IIA significantly inhibits the proliferation of several types of tumors, blocks the cell cycle, induces apoptosis and autophagic death, in addition to inhibiting cell migration and invasion. Among these, the regulation of tumor-cell apoptosis signaling pathways is the key breakthrough point in several modes of antitumor therapy. The PI3K/AKT/MTOR signaling pathway and the JNK pathway are the key pathways for tanshinone IIA to induce tumor cell apoptosis. In addition to glycolysis, reactive oxygen species and signal transduction all play an active role with the participation of tanshinone IIA. Endogenous apoptosis is considered the main mechanism of tumor apoptosis induced by tanshinone IIA. Multiple pathways and targets play a role in the process of endogenous apoptosis. Tanshinone IIA can protect chemotherapy drugs, which is mainly reflected in the protection of the side effects of chemotherapy drugs, such as neurotoxicity and inhibition of the hematopoietic system. Tanshinone IIA also has a certain regulatory effect on tumor angiogenesis, which is mainly manifested in the control of hypoxia. Our findings indicated that tanshinone IIA is an effective treatment agent in the cardiovascular field and plays a significant role in antitumor therapeutics. This paper reviews the pharmacological potential and inhibitory effect of tanshinone IIA on cancer. It is greatly anticipated that tanshinone IIA will be employed as an adjuvant in the treatment of various cancers.